Bangladesh Development Update, October 2018 : Powering the Economy Efficiently - World Bank (World Bank, Washington, DC, 2018)
Strong growth, driven by consumption and public investment, has continued. Macroeconomic stability is strained. Inflation has picked up, driven by food price increases initially and by non-food inflation more recently. Notwithstanding rebound in garment exports and remittances, the current account deficit has widened significantly because of a surge in imports. A large increase in the disbursement of medium and long-term loans helped contain pressure on foreign exchange reserves and moderate the depreciation of the exchange rate. Monetary growth has been subdued because of decline in public sector borrowing from banks and reduced net international reserves, creating room for increased private sector credit growth. However, weak deposit growth and the persistence of high levels of non-performing loans have led to rise in lending rates. The fiscal deficit has increased despite underspending on public investment as revenue growth fell well short of the budget target. Excessive reliance on expensive saving instruments to finance the budget deficit has continued.Over the near-term, growth is expected to remain resilient, underpinned by strong domestic demand. Inflation is likely to accelerate with rising aggregate demand resulting in part from election related increase in private spending, an expansionary fiscal policy and depreciating exchange rate. The current account deficit and the fiscal deficits are projected to widen, but the risks of both external and public debt distress are low. Downside risks include fiscal slippages aggravated by drying up of assistance for supporting the Rohingyas, delays in banking reforms, loss of monetary policy predictability due to diminished central bank independence and weakening reform momentum in the run-up to the elections. Moving forward, creating more and better jobs by boosting private investments, diversifying exports and building human capital remain the top most policy priorities. In addition to handling macroeconomic imbalances through increased flexibility in the exchange rate and interest rates, this would require ensuring a predictable and efficient system of business regulation, faster progress on the implementation of the mega infrastructure projects, improving financial sector governance, and ensuring an adequate and reliable supply of electricity.